1985
DOI: 10.1212/wnl.35.12.1708
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease in the People's Republic of China

Abstract: A door-to-door survey was carried out in six cities of the People's Republic of China (PRC). There was 100% cooperation with the survey. Among 63,195 screened individuals, there were 392 prevalent cases of completed stroke and 115 incidence cases. Prevalence ratios and incidence rates for completed stroke showed a south-to-north gradient. The highest point prevalence ratio and incidence rate (age-adjusted to the 1960 US population) were documented in Harbin in northeast PRC (1,249/100,000; 441/100,000/yr). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
71
6

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(92 citation statements)
references
References 0 publications
15
71
6
Order By: Relevance
“…For every successive 10 years after age 55, the CVD rate more than doubled in both sexes.15 Compared with the age 45-54 group, the mortality rate of CVD (only including cerebral hemorrhage and cerebral infarction) in the age 65-74 group increased 19.7 times in rural areas in Tianjin.4 This kind of increasing trend was also observed in a study of urban communities in six cities in China. 16 Hypertension was the other important risk factor for CVD mortality. Hypertension has been independently associated with CVD mortality worldwide.17-20 A history of hypertension was also reported as a primary risk factor of CVD among men in Shanghai.21 Elevated blood pressure was a firmly established risk factor for CVD mortality.19 Geographic gradient for mortality rate of CVD paralleled the prevalence of hypertension in China.2 In a 15-year cohort study conducted in Finland, according to multivariate analysis, it was found that the relative risk of CVD mortalities for people who had hypertension (SBP>=160mmHg and DBP>=95mmHg) were elevated 3.5-fold and 4.5-fold, compared to those who had normal blood pressure (SBP<160mmHg and DBP<95mmHg) in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…For every successive 10 years after age 55, the CVD rate more than doubled in both sexes.15 Compared with the age 45-54 group, the mortality rate of CVD (only including cerebral hemorrhage and cerebral infarction) in the age 65-74 group increased 19.7 times in rural areas in Tianjin.4 This kind of increasing trend was also observed in a study of urban communities in six cities in China. 16 Hypertension was the other important risk factor for CVD mortality. Hypertension has been independently associated with CVD mortality worldwide.17-20 A history of hypertension was also reported as a primary risk factor of CVD among men in Shanghai.21 Elevated blood pressure was a firmly established risk factor for CVD mortality.19 Geographic gradient for mortality rate of CVD paralleled the prevalence of hypertension in China.2 In a 15-year cohort study conducted in Finland, according to multivariate analysis, it was found that the relative risk of CVD mortalities for people who had hypertension (SBP>=160mmHg and DBP>=95mmHg) were elevated 3.5-fold and 4.5-fold, compared to those who had normal blood pressure (SBP<160mmHg and DBP<95mmHg) in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…35 The major type of stroke in Taiwan is cerebral infarction while for Japan and China, it is cerebral haemorrhage. 36,37 In Japan twice as many men (2.1) and women (2.6) die from stroke as from CAD. Chonghna et al 38 found that the incidence of stroke is four times that of acute myocardial infarction in some areas of China.…”
Section: Burden Of Cardiovascular Disease In Asiamentioning
confidence: 99%
“…Stroke is the third most common leading cause of death worldwide and is a major cause of serious long-term disability in adults [1,2]. In China, the three most common causes of death are vascular disease, cancer and chronic respiratory disease [3].…”
mentioning
confidence: 99%